Translating Treg Therapy in Humanized Mice - Hahn, Susanne A.; Bellinghausen, Iris; Trinschek, Bettina; Becker, Christian (Frontiers in Immunology, 2015)
Regulatory T cells (Treg) control immune cell function as well as non-immunological processes. Their far-reaching regulatory activities suggest their functional manipulation as a means to sustainably and causally intervene with the course of diseases. Preclinical tools and strategies are however needed to further test and develop interventional strategies outside the human body. ‘Humanized’ mouse models consisting of, mice engrafted with human immune cells and tissues, provide new tools to analyze human Treg ontogeny, immunobiology and therapy. Here, we summarize the current state of humanized mouse models as a means to study human Treg function at the molecular level and to design strategies to harness these cells for therapeutic purposes.